PENGARUH PENDEKATAN PENDIDIKAN MATEMATIKA REALISTIK INDONESIA TERHADAP HASIL BELAJAR SISWA KELAS VB SD INPRES FATUKOA PADA MATERI BANGUN RUANG KUBUS DAN BALOK - Kaunan, Aviliana Tike; Nenohai, Juliana M. H.; Benu, Adam Bol Nifu (Universitas Nusa Cendana, 2024)
The goal of this study is to determine the significance of the PMRI approach in helping class VB students understand cubes and blocks. The research was conducted at SD Inpres Fatukoa, Kupang City, using a quantitative approach with a pre-experimental design and a one-group pretest-posttest design type. The research instruments used are pretest and posttest questions. Research findings show that the PMRI approach has a strong influence on student learning outcomes, with an average after-treatment of 78.33. Data analysis with paired sample t-test on SPSS version 21 resulted in a significance value of 0.000 < 0.05, which shows that the PMRI approach has a significant effect on student learning outcomes in the geometry of cubes and blocks.